2021
DOI: 10.1016/j.bbr.2021.113246
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of DAT gene promoter modulates the risk of externalizing and internalizing behaviors on a normative population: An explorative study

Abstract: Accumulating research addressed epigenetic modifications and their role on behavioral phenotypes. We recently proposed to study methylation dynamics of two CpG motifs within the 5'-UTR of dopamine transporter (DAT) gene. Starting from a normative population sample of young adults, we selected three sub-groups based on their prevalent symptoms: subjects were assigned to Internalizing, Externalizing and Lowrisk sub-groups according to elevated scores in specific phenotypic scales. Using a new approach, we calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…The new approach based on cross-correlation of CpG loci, which was already studied on ADHD [21] and Parkinson's disease [22], was applied in this research focused on vulnerability to Internet addiction disorder. Some of these results found confirmation from other previous research, for example, the positive correlation between CpG2 and CpG3 which was also found in studies by Carpentieri et al [36] and by Tafani et al [22]. For the first time, an association was noted between the 3'-UTR genotype and a 5'-UTR intra-motif link (from the CpG5-CpG6 comparison).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The new approach based on cross-correlation of CpG loci, which was already studied on ADHD [21] and Parkinson's disease [22], was applied in this research focused on vulnerability to Internet addiction disorder. Some of these results found confirmation from other previous research, for example, the positive correlation between CpG2 and CpG3 which was also found in studies by Carpentieri et al [36] and by Tafani et al [22]. For the first time, an association was noted between the 3'-UTR genotype and a 5'-UTR intra-motif link (from the CpG5-CpG6 comparison).…”
Section: Discussionsupporting
confidence: 87%
“…The aspects of Internet addiction that lead to aggressive behaviors are externalizing phenotypes included in Achenbach's definition [38]. Therefore, we can hypothesize that the same positive relationship between CpG3 and CpG5 can be found in both the externalizing subgroup of the previous work [36] and in the high IAT subgroup of the current work. From scatterplot graphics, methylation levels in positions 3 and 5 seem to follow an ascendent line in the high IAT group and are negatively matched in control groups, particularly in genotype 10/10.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Adolescents who reported more externalizing problems from age 13 to 17 years tended to show a larger epigenetic age than chronological age (higher EA) at age 17 years. Previous studies have found links between externalizing symptoms and DNAm Carpentieri et al, 2021;Cicchetti & Handley, 2017) However, the only study we located that examined the links between externalizing symptoms and EA found a positive link with inflammation-related methylation profiles, but not with epigenetic age . Thus, to the best of our knowledge, this is the first study showing the potential effects of preceding externalizing problems on EA.…”
Section: Discussioncontrasting
confidence: 55%
“…Our own studies on ADHD take into consideration the methylation pattern in the 5′-UTR of the DAT1 gene [ 10 ]. The correlation between methylation patterns in the 5′-UTR of the DAT1 gene and psychopathological condition or addiction has been widely used in previous studies [ 11 , 12 , 13 ]. In our last papers [ 14 , 15 ], we investigated whether the methylation pattern in the DAT1 gene (including the opposed DNA strand) can be influenced by the allelic genotype at 3′-UTR.…”
Section: Introductionmentioning
confidence: 99%